Perlakuan Akuntansi Piutang Air pada PDAM di Jombang (Studi Kasus PDAM Tirta Kencana Kabupaten Jombang) - Krisna Anggraini; Rachma Agustina (JFAS : Journal of Finance and Accounting Studies, 2020)
PDAM's income is obtained from the distribution of clean water to customers which is done on credit. Water receivables are the main contribution to PDAM Tirta Kencana of Jombang Regency. The research has a purpose to determine the accounting treatment of water receivables at PDAM Tirta Kencana is it in accordance with SAK ETAP or not. The method used is a qualitative method with a case study approach. The results showed the accounting treatment of water receivables at PDAM Tirta Kencana was in accordance with SAK ETAP. Water receivables are recognized when the List of Billed Water Accounts (DRD-A) is issued. Water receivables are recorded based on water meter readings.Water receivables are recorded based on water meter readings. Water receivables are valued at a number of receivables that can be collected. Water receivables are presented on the balance sheet as current assets. Allowance for water receivables is calculated in Time Series.